2018
DOI: 10.1027/1614-0001/a000256
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between the Behavioral Approach System (BAS) and Self-Reported Life History Traits

Abstract: Abstract. The behavioral approach system (BAS) has been shown to be important in everyday life. However, its putative evolutionary origins have not been extensively studied. The purpose of this study was to explore relationships between BAS processes and life history strategies, or lifestyles, within life history theory. The BAS scales were assessed by the Reinforcement Sensitivity Theory of Personality Questionnaire (RST-PQ) and Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ-20), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 55 publications
3
2
0
Order By: Relevance
“…Finally, Reward Reactivity predicted intrinsic motivation. These data are in line with previous studies that have consistently related this scale to prosocial tendencies, such as commitment to a romantic partner and care for relatives (Krupić et al, 2018;.…”
Section: Intrinsic Goalssupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, Reward Reactivity predicted intrinsic motivation. These data are in line with previous studies that have consistently related this scale to prosocial tendencies, such as commitment to a romantic partner and care for relatives (Krupić et al, 2018;.…”
Section: Intrinsic Goalssupporting
confidence: 92%
“…RST-PQ Impulsivity showed a similar pattern of correlations, but was lower in magnitude as compared with SR. These findings are in line with past studies examining relationships between SR and evolutionarily-evolved motives and the fast lifestyle within life history theory (LHT) (Krupić et al, 2018). Thus, our findings suggest that high SR individuals are motivated by extrinsic rewards, which might explain why their behaviour is directed towards resources and is accompanied by a lack of concern for the social environment.…”
Section: Extrinsic Goalssupporting
confidence: 91%
See 1 more Smart Citation
“…This is reasonable to assume, since the opioid system has strong impact on social emotions and behaviour (Machin & Dunbar, 2011;Panksepp, Herman, Vilberg, Bishop, & DeEskinazi, 1980;Vanderschuren, Niesink, & Van Ree, 1997), infant attachment behaviour (Kalin, Shelton, & Lynn, 1995;Moles, Kieffer, & D'Amato, 2004), and relationship with kin (D'amato & Pavone, 1993). These findings are well in line with the study relating self-report measures of liking and cooperative motives and quality relationship with others as an aspect of slow lifestyle (Krupić et al, 2017). In addition, Elvemo, Landrø, Borchgrevink, & Haberg (2015) recently found that the liking (measured by Reward responsiveness) is reduced in chronic pain patients, which they interpret as a manifestation of a low level of opioids.…”
Section: Liking and Opioidsupporting
confidence: 78%
“…One of the rare studies that used both testosterone and the BAS scales representing wanting revealed that both are related to a number of a fast lifestyle correlates: low social sensitivity (Yildirim & Derksen, 2012), mistrust, low social bonding and social aggression (Bos, Terburg, & van Honk, 2010;Terburg et al, 2009). On the other hand, wanting has been found to correlate with fast lifestyle (Krupić, Banai, & Corr, 2017) and negatively with cooperative motives (e.g. kin altruism, mutual exchange, etc.)…”
Section: Fast Lifestylementioning
confidence: 99%